2014
DOI: 10.1093/brain/awu190
|View full text |Cite
|
Sign up to set email alerts
|

Perforant path synaptic loss correlates with cognitive impairment and Alzheimer's disease in the oldest-old

Abstract: Alzheimer's disease, which is defined pathologically by abundant amyloid plaques and neurofibrillary tangles concurrent with synaptic and neuronal loss, is the most common underlying cause of dementia in the elderly. Among the oldest-old, those aged 90 and older, other ageing-related brain pathologies are prevalent in addition to Alzheimer's disease, including cerebrovascular disease and hippocampal sclerosis. Although definite Alzheimer's disease pathology can distinguish dementia from normal individuals, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
111
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 142 publications
(120 citation statements)
references
References 40 publications
8
111
0
1
Order By: Relevance
“…This loss was prevented to some degree by liraglutide treatment. Synapse loss is commonly observed in human AD brains [38]. This loss of connections between neurons is most likely the reason for the loss of cognitive function in AD patients.…”
Section: Discussionmentioning
confidence: 99%
“…This loss was prevented to some degree by liraglutide treatment. Synapse loss is commonly observed in human AD brains [38]. This loss of connections between neurons is most likely the reason for the loss of cognitive function in AD patients.…”
Section: Discussionmentioning
confidence: 99%
“…This change has been mainly interpreted as being the result of loss of afferents to the DG and to the loss of neurons in the CA1 region of the hippocampus (107). However, morphological and immunohistochemical studies have shown reduced dendritic arbors, reduced numbers of synapses, and reduced synaptic protein markers both in the CA1 region of the hippocampus and in the DG (32,36,56,82,(86)(87)(88)(89).…”
Section: Final Commentsmentioning
confidence: 99%
“…Mice deficient in SV2A develop seizures and die within 3 wk of birth (4). In addition to its well-established role as the target for the antiepileptic drug levetiracetam (5,6), dysfunction of SV2A has been implicated in other neurologic disorders such as Alzheimer's disease (7)(8)(9).…”
mentioning
confidence: 99%